Tattoo reactions as the initial presentation of lepromatous leprosy and cutaneous sarcoidosis: Report of two cases - Geeti Khullar; Niti Khunger; Khushpreet Kaur Mann; Sharma Shruti (Wolters Kluwer Medknow Publications, 2019)
There has been a rising trend of tattooing in the recent years, resulting in an increased incidence of cutaneous adverse effects. A wide range of infectious and noninfectious dermatoses have been described to occur within tattoos. Cutaneous complications developing in tattooed skin as the initial manifestation of the disease are uncommon. We describe two interesting cases with black tattoo-related reactions as the presenting feature of lepromatous leprosy and cutaneous sarcoidosis, respectively.